2013
DOI: 10.1016/j.nonrwa.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Pattern formation driven by cross-diffusion in a 2D domain

Abstract: In this work we investigate the process of pattern formation in a two dimensional domain for a reaction-diffusion system with nonlinear diffusion terms and the competitive Lotka-Volterra kinetics. The linear stability analysis shows that cross-diffusion, through Turing bifurcation, is the key mechanism for the formation of spatial patterns . We show that the bifurcation can be regular, degenerate non-resonant and resonant. We use multiple scales expansions to derive the amplitude equations appropriate for each… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
75
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(75 citation statements)
references
References 48 publications
0
75
0
Order By: Relevance
“…In order to accurately predict the spatial features of the expected Turing patterns, non-linear bifurcation analysis and the amplitude equations formalism must be used, see i.e. [19,22,29,30]. Nevertheless, this kind of analysis is beyond the scope of the present paper, for this reason we resorted to numerical investigation of pattern selection issues.…”
Section: Numerical Investigationsmentioning
confidence: 99%
“…In order to accurately predict the spatial features of the expected Turing patterns, non-linear bifurcation analysis and the amplitude equations formalism must be used, see i.e. [19,22,29,30]. Nevertheless, this kind of analysis is beyond the scope of the present paper, for this reason we resorted to numerical investigation of pattern selection issues.…”
Section: Numerical Investigationsmentioning
confidence: 99%
“…In developmental biology, recent experimental findings demonstrate that cross-diffusion can be quite significant in generating spatial structure [10]. The effects of cross-diffusion on models for pattern formation (i.e., reaction-diffusion type) have been studied in many theoretical papers [13][14][15][16][17][18][19][20][21][22][23][24]. Recently, in [25] we showed that introducing cross-diffusion to a system of reaction-diffusion equations results in further relaxation of the conditions necessary for the emergency of patterns.…”
Section: Introductionmentioning
confidence: 99%
“…An important number of contributions have been proposed to treat systems like (1.1) from a numerical perspective, either considering or not the cross-diffusion effect (see [2,5,6,8,14,18,21,39] for finite differences, finite volumes, spectral and finite element methods for the spatial discretization). Here, and following [11,27,37], we propose a new finite volume element (FVE) method for the numerical approximation of the underlying reaction-cross-diffusion system.…”
Section: Introductionmentioning
confidence: 99%